1999
DOI: 10.1007/pl00010285
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the Hypericin Sensitized Photooxidation of Bilirubin IXα

Abstract: In aerated protic solvents like ethanol or 80% aqueous ethanol, bilirubin IX was found to undergo a hypericin sensitized oxidative photodestruction. By means of quenching experiments it was deduced that this was mainly due to the sensitized production of singlet oxygen, but also to some extent to the sensitized formation of superoxide radicals which then react with bilirubin IX. In absence of oxygen, a photochemically induced disproportionation reaction of hypericin may lead to the oxidative degradation of bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This is quite large compared with the only 5 nm of (3À) 1 [9]. However, hypericin sensitized photooxidation of bilirubin, which has been shown to provide a sensitive measure of the generation of sensitized active oxygen species ± in peculiar of singlet oxygen and superoxide radicals [10] ± revealed that (3À) 12 did not produce the sensitized singlet oxygen and superoxide species thought to be the most active agents in hypericin photodynamic therapy [1] (Fig. At this point the use of 12 as a photodynamic agent seemed even more promising since a low uorescence quantum yield could point to an enhanced intersystem crossing, which would be necessary to sensitize active oxygen species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is quite large compared with the only 5 nm of (3À) 1 [9]. However, hypericin sensitized photooxidation of bilirubin, which has been shown to provide a sensitive measure of the generation of sensitized active oxygen species ± in peculiar of singlet oxygen and superoxide radicals [10] ± revealed that (3À) 12 did not produce the sensitized singlet oxygen and superoxide species thought to be the most active agents in hypericin photodynamic therapy [1] (Fig. At this point the use of 12 as a photodynamic agent seemed even more promising since a low uorescence quantum yield could point to an enhanced intersystem crossing, which would be necessary to sensitize active oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…1 H and 13 C NMR, UV/ Vis,¯uorescence, and mass spectra were recorded using Bruker DRX 500 and DPX 200, Hewlett Packard 8453 UV/ Vis, Hitachi 4010F, and Hewlett Packard 59987 quadrupole instruments. [10]. The¯uorescence quantum yield was determined as described previously [9].…”
Section: Methodsmentioning
confidence: 99%
“…The production of singlet oxygen ⁄ oxidizing species by 11-14 was monitored by bilirubin-IXa-degradation according to Ref. (43). The long-wavelength ''hypericinic'' absorption band intensities of 1 and the four compounds were made equal by adjusting concentrations to provide comparable light absorptions for all compounds investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Photodestruction of bilirubin IX␣. Following Hagenbuchner and Falk (11) irradiation of the thermostated (20.0 Ϯ 0.1ЊC) aerated solutions of sodium bilirubinate, together with 1 Ϫ or 2 Ϫ in 80% aqueous ethanol contained in SiO 2 cuvettes (d ϭ 1 cm), were performed by means of a 300 W tungsten lamp and a cut-off filter blocking light below 570 nm and measuring the UV-Vis spectra at intervals of 20 s (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…To test for an enhanced photochemical singlet oxygen/ superoxide radical formation of 2 in comparison to 1 we used the recently introduced photosensitized bilirubin IX␣ destruction method (11). As shown in Fig.…”
Section: Heavy-atom Substitutionmentioning
confidence: 99%